PENGARUH KOMITMEN ORGANISASIONAL TERHADAP KINERJA GURU DIMODERASI OLEH KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DAN LINGKUNGAN KERJA DI SMK KABUPATEN PEMALANG - Wasito, Edy; Suhari, Yohanes (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study was to examine the transformational leadership and work environment moderate the effect of organizational commitment on teacher performance. Usefulness of the research is to explain and extend previous research on transformational leadership and work environment moderate the effect of organizational commitment on teacher performance. The research data is primary data collected directly from the respondents to the questionnaire. The results showed that transformational leadership moderates the influence of organizational commitment on teacher performance and the work environment moderate the effect of organizational commitment on teacher performance. Keywords: transformational leadership, work environment, organizational commitment, performance of teachers.